COVID-19 impairs oxygen delivery by altering red blood cell hematological, hemorheological, and oxygen transport properties - Rogers, Stephen C.; Brummet, Mary; Safari, Zohreh; Wang, Qihong; Rowden, Tobi; Boyer, Tori; Doctor, Allan (Frontiers in Physiology, 2024)
Coronavirus disease 2019 (COVID-19) is characterized by impaired oxygen (O2) homeostasis, including O2 sensing, uptake, transport/delivery, and consumption. Red blood cells (RBCs) are central to maintaining O2 homeostasis and undergo direct exposure to coronavirus in vivo. We thus hypothesized that COVID-19 alters RBC properties relevant to O2 homeostasis, including the hematological profile, Hb O2 transport characteristics, rheology and the hypoxic vasodilatory (HVD) reflex.RBCs from 18 hospitalized COVID-19 subjects and 20 healthy controls were analyzed as follows: (i) clinical hematological parameters (complete blood count; Hematology analyzer), (ii) O2 dissociation curves (p50, Hill number, Bohr plot; HEMOX analyzer), (iii) rheological properties (osmotic fragility, deformability, and aggregation; LORRCA ektacytometry), and (iv) vasoactivity (the RBC HVD; vascular ring bioassay).Compared to age and gender matched healthy controls, COVID-19 subjects demonstrated: (1) significant hematological differences (increased WBC count -with higher percentage of neutrophils), RBC distribution width (RDW), and reduced hematocrit, Hb concentration, MCV, and MCHC), (2) impaired O2 carrying capacity and O2 capacitance (resulting from anemia) and no difference in p50 or Hb O2 co-operativity, (3) compromised regulation of RBC volume (altered osmotic fragility), (4) reduced shear induced RBC deformability, (5) accelerated RBC aggregation kinetics, and (6) no change in the RBC HVD reflex. When considered collectively, homeostatic compensation for these RBC impairments requires that the cardiac output in the COVID cohort would need to increase by ~ 135% to maintain O2 delivery similar to that in the control cohort.Additionally, the COVID-19 disease RBC properties were found to be exaggerated in blood type O hospitalized COVID-19 subjects, compared to blood type A.These data indicate that hospitalized COVID-19 subjects present with altered RBC features, sufficient to create a significant burden upon the cardiovascular system to maintain O2 delivery homeostasis, which appears exaggerated by blood type (more pronounced with blood type O), and likely plays a role in disease pathogenesis.